TEACHING PRACTICE GUIDANCE BY USING THE APPRECIABLE MODEL’S METHOD TO ENHANCE THE TEACHING SKILL UPON SCIENTIFIC SUBJECT TOWARD TEACHER’S CANDIDATE AS AN EFFORT TO RAISE ITS QUALITY - SUCIATI SUDARISMAN (Bioedukasi: Jurnal Pendidikan Biologi, 2005)
Study on implementation of teaching practice guidance by using the appreciable model's method has been carried out in order to enhance the teaching skill of a teacher’s candidate in teaching the scientific subject. The mode! 'applied by the candidates during teaching was created by the supervisors. The study it self was'carried out during the student s practice of teaching in 3 junior high school, supervised by 3 lecturer and 3 senior teachers. The candidates were then asked to make the review toward that method and disscuss it with the supervisor.The results indicated that the appreciable model’s method could be as an alternative method used by the candidate and supervisor during the guidance of teacher’s candidate. It was showed by the raising of the candidate 's skill in making the teaching materials preparation, and also the teaching skill respectivelly.